La guerre économique à l’ombre de la crise : le cas français - Axelle Degans (L'Espace Politique, 2018)
The economic war is a concept that has long been poorly accepted at the ideological level, and little taken into account by the political elites. It shocks liberals, supporters of free trade, as well as political elites attached to the unity of the Western bloc, and yet France has undeniably been affected by deindustrialization since the economic crisis of the 1970s. Moreover, some French companies have been the victims of this economic war. This is bringing a slow awareness in France of an inconvenient reality. Actually, what is at stake is to be able to keep jobs and the standard of living of the French population. The fields of the economic war are evolving into law and the cyber sphere, which requires strong political adaptability and will.